Meaning and scope of anthropology in their relation to philosophy - Wierciński, Andrzej (Anthropological Review, 1980)
The essence of philosophy consists in the attempts of rationalizing the general world’s model, a position of man within it and the meaning of man’s activities. This model is expressed verbally in highly abstractous notions. The complete products of such philosophical reflection are philosophical systems which embrace: 1) general truths about the world (ontology), 2) the ways of their acquiring (gnoseology and logics) and 3) the ways and means for the realization of human aims Le. the general strategy of human behavior (philosophical anthropology with axiology and ethics). The anthropology is the science which consists in an adequate description and interpretation of the course of the process of human evolution in its biological and cultural properties. Thus, the philosophy differs much from the anthropology as regards fits scope and procedure of solving the problems. It arose far much earlier ie. in the I millennium B.C. while anthropology could evolve only after C. Darwin. The extent of philosophical generalisations and their introduction into the ideological regulation of the social life have caused well known determinants of anthropological theorizing. On the other hand, anthropology aims to define ’ the adaptative role of philosophy and determinants of its genesis and development.